Design Of Android-Based Cctv Monitoring Application At The Garut Regency Command Center Using Rapid Application Development Method - Rahayu, Dinar; Umamah, Ai; Abdullah Munawar, Febri (RISTEC : Research in Information Systems and Technology, 2024)
This research aims to develop an Android-based CCTV monitoring application for the Command Center of Garut Regency using the Rapid Application Development (RAD) Method. The application addresses the issues of inefficient real-time security monitoring and limited mobile device access. RAD was chosen due to its capability for rapid and responsive development according to user needs. The outcome is an application that visualizes CCTV devices deployed across various locations. Data integration from these CCTV sources enables operators to efficiently monitor security situations. System testing, conducted through black box testing, validated the functionality of the application, demonstrating the successful implementation of the RAD method in its development. In conclusion, this CCTV monitoring application effectively enhances security monitoring efficiency in Garut Regency. The utilization of RAD accelerates application development and ensures alignment with user requirements. Consequently, this application can serve as an effective solution for improving security in the region.